Rancang Bangun Alat Sentrigufal Pencuci Daging Buah Kelapa Menggunakan Cairan Air Kelapa (Pre-Processing Metode Sentrifugasi) - Santosa, Hadi; ., Yuliati; Mulyana, Ig. Jaka (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2020)
The diversification of the coconut processing industry into Virgin Coconut Oil (VCO) as a more prospective coconut derivative is currently still growing rapidly. VCO is a virgin coconut oil product that is beneficial for health, and can be used as a raw material for natural cosmetics which has high economic value. Preliminary research has successfully designed the construction of a coconut husk peeler and a coconut shell breaker machine as an early stage in the VCO production process technology. The discussion of this paper covers the design of a coconut meat washing machine utilizing coconut water which consists of a rotating tube with an adjustable tube rotation speed with an inverter and an electric motor as the driving force equipped with a high pressure nozzle with ± 75 psi pressure. Inside the tube there is a retaining divider that regulates the flow of the washed coconut meat. The washing process uses coconut water to wash coconut meat in a washing tube that rotates at a certain speed as needed with a capacity of 8 kg timer for ± 3-5 minutes. Coconut water is drained and coconut meat is ready for the next process.